Structural, optical, and electrochemical investigation on cobalt ferrite nanoparticles synthesized using Punica granatum peel extract - J. Josephine Synthiya; K. Arumugapriya; R. Mary Jenila; J. Shakina (Next Materials, 2025)
Developing advanced electrode materials for electrochemical energy storage is crucial for next-generation supercapacitors and related applications. A simple and eco-friendly green synthesis approach is adopted to synthesize cobalt ferrite (CoFe₂O₄) nanoparticles, utilizing Punica granatum peel extract as a natural alternative to conventional hazardous chemicals typically used as stabilizing, reducing, and capping agents. This study investigates the optical, structural, and electrochemical properties of CoFe₂O₄ nanoparticles. The structural analysis conducted using X-ray diffraction (XRD) verifies the successful formation of the spinel CoFe₂O₄ phase, confirming its crystallographic structure. Scanning electron microscopy (SEM) reveals spherical, agglomerated CoFe₂O₄ nanoparticles. Energy-dispersive X-ray spectroscopy (EDAX) analysis is conducted to verify the elemental composition of Co, Fe, and O, ensuring the successful formation of CoFe₂O₄ nanoparticles. X-ray photoelectron spectroscopy (XPS) verifies the oxidation states of Co²⁺, Co³ ⁺, and Fe³ ⁺, which contribute to charge storage mechanisms. Vibrating sample magnetometry (VSM) analysis indicates the superparamagnetic behavior with a saturation magnetization of 72.99 emu/g. The cyclic voltammetry analysis exhibited quasi-rectangular curves, signifying ideal pseudocapacitive characteristics, with a capacitance value of 202 F/g. These results confirm that the bio-assisted synthesis offers a green and sustainable route for synthesizing CoFe2O4 nanoparticles. Compared to conventional methods, the green synthesised CoFe₂O₄ nanoparticles with a reduced crystallite size, higher saturation magnetization, and enhanced specific capacitance, demonstrating improved structural, magnetic, and electrochemical properties.